Menumbuhkan Motivasi Dan Pengamalan Agama Anak Usia Sekolah Di Desa Parupuk Julu Melalui Kegiatan Pesantren Kilat - Harahap, Sumper Mulia; Ritonga, Raja; Panggabean, Rizky Mubarok; Hasibuan, Ahmad Jasa; Mahyuddin Mahyuddin; Aida Sapitri; Srg, Kartina; Hasibuan, Nur Asiah; Lubis, Nurhidayah; Rabiatul Adawiyah; Rangkuti, Rosipa Rahmi (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
Children's education patterns are often related to the methods and processes carried out. The continuous mentoring model is a very good method. Along with this method, the process of approaching children will run smoothly. Children in Parupuk Julu village in North Padang Lawas Regency have very little assistance in the form of learning outside of school. The Service Team from the STAIN Mandailing Natal Campus carried out service activities by assigning a group of Real Work Study students to the village. This is done to provide assistance to school age children in enhancing their learning experience. The method used is intense mentoring carried out by students with the concept of group learning in the Pesantren Kilat event. The results of the service show that intensive mentoring increases children's motivation in learning. They have been able to instill every practical task of worship taught at Pesantren Kilat activities, such as writing hijaiyah letters, reading iqra, reading the Koran, performing prayer movements and reading. So, the intense mentoring method carried out by STAIN Mandailing Natal KKN students resulted in increasing the motivation and religious practice of children in Parupuk Julu village.